Chronotope, technology affordances, and task design: using WeChat to facilitate Chinese learning in the classroom - Wang Xuan (Journal of China Computer-Assisted Language Learning)
This paper makes a case for the Bakhtinian concept of “chronotope” in explaining the space–time affordances of technology in second language pedagogy. It examines the production of space–time that intersects online/offline, formal/informal and local/translocal activities in task-based language teaching. Drawing on an example of instructional design using WeChat to facilitate the learning of business Chinese, this paper illustrates that the chronotopic affordances of mobile apps such as WeChat, when creatively integrated with task-based language pedagogy, can significantly expand the learning mobility and opportunities defined by the classroom in its traditional sense. This chronotopic expansion enables learners to be positioned in digitally mediated and simulated scenarios and roles that transcend the space–time of the classroom, closely resembling real-world communication in the globalising world. It is suggested that language task design, taking into account the chronotopic affordances of technology, can facilitate authentic and networked space–time of learning by embedding it in mobile, hybrid, individualised and collaborative contexts. The chronotope concept helps us not only critically understand the complexity of mobile-assisted language learning but also theoretically reimagine the classroom chronotopes and the roles, relationships and processes of learning in an increasingly technology-based knowledge economy in post-pandemic education.